INCLUSIVE EDUCATION SYSTEM FOR SPECIAL CHILDRENS NEEDS - Anggeriyanti, Wahyuni (JOEEL (Journal of English Education and Literature), 2020)
The aim of this study is to reveal the teachers understanding of basic concepts in inclusive education and the approaches they require to be competent on it. The study is supported by qualitative case study that is considered relevant to the phenomena of the study. The case to be studied is a primary school which proposes an inclusive education for children with educational needs that consists of four students in primary one and two teachers. The data is based on one-by-one interview guidelines, observation and document analysis. The component of findings and discussions consist of classroom management, teaching approach, social interaction and assessment. It can be concluded that the concept of inclusive education is a school program for all students with various background which is interpreting interaction and learning repetitively. Throughout the inclusive education, students with special education have access to enrich academic and social performance. The suggestion of study is for educators that should teach students in collaboration strategy and institution has a reference for future study on similar problem. The conclusion is that inclusive education is one of the options in providing alternative education. It is time for decision-makers apply any kinds of input to present education for all.